YOGYAKARTA DALAM FOTOGRAFI IMPRESIONISME - Wiwid Widya Apriyadi; Arti Wulandari; Oscar Samaratungga (Institut Seni Indonesia Yogyakarta, 2021)
Yogyakarta in The Impressionism Photography. The creation of photographic works with the title “Yogyakarta in Impressionism Photography” aims to present the scenery of Yogyakarta area using photographic techniques that look like an impressionist painting. The main objects in these photographic works are historical and natural tourist attractions in Yogyakarta area. The intensity of experience and feeling conveyed in this creation of photographic work are the feeling of boredom of the routines that are carried out in photographing, especially taking landscape photography. The method implemented for the photo creation was to have exploration and experimentation in photographing landscapes. Exploration and experimentation are conducted by moving the camera around the object or moving the camera during the image recording process. The result of the creation of this artwork is that photographic works resemble the impressionist paintings. ABSTRAKPenciptaan karya fotografi dengan judul